2000
DOI: 10.1200/jco.2000.18.7.1492
|View full text |Cite
|
Sign up to set email alerts
|

Second Malignant Neoplasms After Treatment for Hodgkin’s Disease in Childhood or Adolescence

Abstract: Successfully treated children and adolescents with Hodgkin's disease have a substantial risk for the occurrence of subsequent neoplasms. The most frequent SMNs (skin, thyroid, and breast) are readily detected by physical examination and available screening procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(74 citation statements)
references
References 39 publications
5
69
0
Order By: Relevance
“…36,37 Others have shown a high risk of secondary NHL in the first year after treatment initiation, which declines in the next 5 years, and peaks in the subsequent 10 to 14 years, 37,38 but might continue to occur in patients having long follow-ups. Green et al 39 reported a cumulative incidence of 4.62% for secondary NHL 30 years after diagnosis of nodular sclerosing HL. Van Leeuwen, 37 however, observed the highest incidence of 5.9% AE 2.1% in 744 patients with HL, at a median interval of 13.3 years between HL diagnosis and secondary NHL.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Others have shown a high risk of secondary NHL in the first year after treatment initiation, which declines in the next 5 years, and peaks in the subsequent 10 to 14 years, 37,38 but might continue to occur in patients having long follow-ups. Green et al 39 reported a cumulative incidence of 4.62% for secondary NHL 30 years after diagnosis of nodular sclerosing HL. Van Leeuwen, 37 however, observed the highest incidence of 5.9% AE 2.1% in 744 patients with HL, at a median interval of 13.3 years between HL diagnosis and secondary NHL.…”
Section: Discussionmentioning
confidence: 99%
“…8 Cohorts of Hodgkin's patients of any stage suggest that this difference is much higher. 8,[11][12][13][14][15][16][17]39 However, patients who relapse have a more pronounced risk of secondary malignancies according to a cohort study by Aleman and colleagues. 16 Therefore, the addition of radiotherapy which reduces the number of patients with relapse (who require more aggressive therapy) may contribute to a smaller overall risk difference than suggested by the cohorts who do not distinguish between relapsed and non-relapsed patients when evaluating the risk of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…8,11 Risk factors for secondary malignancies and cardiac disease are the choice and dose of chemotherapy and radiotherapy. 8,[11][12][13][14][15][16][17] Unfortunately, long-term comparisons of combined modality treatment with chemotherapy alone (CT-alone) are difficult in cohorts of Hodgkin's survivors. Nonetheless, to avoid additional radiation-induced toxicity, chemotherapy-only treatment for patients with early stage HL has been advocated.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report, 28 of 182 former patients with Hodgkin's disease during childhood or adolescence were identi® ed with a SMN (18). We recognized a SMN in four patients (3%) during the observation period.…”
Section: Discussionmentioning
confidence: 99%